Discour sur le Pqpport entre lq Lqgue et L’identite Georgiennes Dans la Litterqture Scientifique Occidentqle - Ghutidze, Inga (Actual Problems of Kartvelology, 2025)
The problem of the relationship between language and identity is one of the most important and difficult problems of recent times, to which numerous studies are devoted. The discourse of the relationship between language and identity will always become the subject of research and discussion by foreign scholars on the example of Georgia, we hope that in the future this will be based on taking into account the objective situation and reliable sources, as well as scientific impartiality.